Numerical Simulation of Deflection and Stability of the Wooden Transmission Tower of Gliwice Radiostation - WOJACZEK, Błażej; KATUNIN, Andrzej; BROL, Janusz; ADAMCZYK, Katarzyna (Engineering Transactions, 2018)
The wooden transmission tower of the Gliwice radiostation is the highest wooden construction around the world. Considering that it is in operation over 80 years it is necessary to properly maintain it to extend its residual life. In order to analyse the most critical elements of the tower as well as to plan the strategy of its maintenance, including repairs and replacements of wooden elements, it is necessary to analyse its deflection and stress distributions under possible loading scenarios. In this paper, the authors presented an overview of history and construction of the tower as well as presented the results of static and buckling numerical simulations to evaluate a condition and a margin of safety, and to find the critical structural elements of this construction. The 3D numerical analysis is performed for the wooden transmission tower of the Gliwice radiostation for the first time. The results of simulations presented in this study indicate acceptable condition of the tower, in particular the resulting stresses under the static loading or buckling are at the level of 18% of the critical stresses according to the assumed geometrical model. However, further studies are necessary to refine numerical model and consider secondary elements of the tower, wood imperfections and other factors that have significant influence on its integrity and safety.